STRATEGI PELAYANAN SEKRETARIAT DEWAN PERWAKILAN RAKYAT KABUPATEN ACEH SELATAN - Fanni Marishah Tanjung; Zuhrizal Fadhly (Universitas Bina Taruna Gorontalo, 2022)
This study aims to find out what strategies the South Aceh DPRK Secretariat has implemented in providing services in accordance with their respective functions and duties and to analyze the extent to which the implementation of the strategy has been carried out. The research method used is a qualitative method. The data sources used are primary and secondary. Data analysis techniques used in the study include: data reduction, data presentation and drawing conclusions. The results showed that the Secretariat of the DPRK Aceh Selatan had implemented various strategies in solving the problems faced, both from the structure development strategy, the development strategy or simplification of the procedure system, the infrastructure development strategy and the culture development strategy. However, in several programs in the strategy items, the implementation has not been fully maximized, including the employee comparative study program which has not been maximally implemented and in the aspect of giving awards to employees who excel, there has not been a written reward set, there are still problems with processing time in proposing damaged facilities and infrastructure so that interfere with employee work. The conclusion that can be drawn from the research is that the secretariat has implemented a service strategy, but its implementation has not been fully maximized.